Stylogaster Macquart, 1835 (Diptera: Conopidae) from Northeastern Brazil: new records and two new species - Rocha, Leonardo Silvestre Gomes; de Mello-Patiu, Cátia Antunes (Zootaxa, 2012)
Of the 69 Neotropical species of Stylogaster, only one record was previously known from Northeastern Brazil (from Bahia state in 1985—S. brasilia Camras & Parrillo). Several specimens from this region housed at the MNRJ collection were studied, mostly from Bahia, Ceará and Pernambuco states. Two new records were obtained: S. macrura Lopes, 1938, previously known from São Paulo state (Southeastern Brazil), and S. souzai Monteiro, 1960, from Amapá and Pará (Northern Brazil). Descriptions of two new species, S. hugoi sp. nov. and S. planitarsis sp. nov. are presented, as well as that of the previously unknown female of S. souzai. Illustrations and geographic distribution of the species are also provided.